2022
DOI: 10.29023/alanyaakademik.1088204
|View full text |Cite
|
Sign up to set email alerts
|

A Case on Volatility and Volatility Spillover in the Turkey’s Foreign Exchange Market

Abstract: Amerika Birleşik Devletleri Merkez Bankası Aralık 2016’da faiz artırım döngüsüne başlamış ve finansal piyasalardaki oynaklık hızlıca artmıştır. Coronavirus (COVID19) salgın ve Türkiye’de 2018 - 2021 döneminde yaşanan kur atakları oynaklık çalışmasının yapılmasına öncülük etmiştir. Çalışmanın amacı Türk Lirası üzerindeki oynaklık ve oynaklık yayılımının EGARCH modeli ile analiz edilmesidir. Asimetrik etki parametresinin (δ), yani kaldıraç etkisinin 15 Aralık 2016 – 28 Şubat 2022 döneminde ABD Doları/Türk Lirası… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The foreign exchange rate volatility in Türkiye is modelled in another study where GARCH(1,1) and EGARCH(1,1) models are employed and it is found out that various policies have similar effects on the foreign exchange rate volatilities (Ayhan, 2006). In another work, the USD/TRY and USD/DM exchange rates in Türkiye are modelled for the 1988-1995 period uaing GARCH models and it is exposed that foreign exchange rate volatilities increase during the economic crisis periods (Aysoy, 1996). Asymmetric Power ARCH (APARCH) models are utilized to represent the foreign exchange (Demirgil and Kesekler, 2019).…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The foreign exchange rate volatility in Türkiye is modelled in another study where GARCH(1,1) and EGARCH(1,1) models are employed and it is found out that various policies have similar effects on the foreign exchange rate volatilities (Ayhan, 2006). In another work, the USD/TRY and USD/DM exchange rates in Türkiye are modelled for the 1988-1995 period uaing GARCH models and it is exposed that foreign exchange rate volatilities increase during the economic crisis periods (Aysoy, 1996). Asymmetric Power ARCH (APARCH) models are utilized to represent the foreign exchange (Demirgil and Kesekler, 2019).…”
Section: Literature Surveymentioning
confidence: 99%
“…The volatility of the MYR/GBP is modelled employing GARCH, EGARCH, GARCH-M and EGARCH-M models and it is shown that GARCH-M model provides the best goodness of fit metric (Chong et al, 2011). In another work, the USD/TRY and DM/TRY exchange rates are modelled employing ARCH and GARCH models and it is concluded that GARCH(1,1) provides the best accuracy (Aysoy et al, 1996). Similarly, the exchange rate volatility in Türkiye is investigated using ARCH, GARCH and SWARCH methods where it is observed that the SWARCH model has high accuracy (Guloglu and Akman, 2007).…”
Section: Literature Surveymentioning
confidence: 99%